Faktor-Faktor yang Memengaruhi Laporan Keuangan Kementerian Negara/Lembaga - Wulandari, Wiwi Prapti; Kuntadi, Cris (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
This study aims to conduct a comprehensive literature review on the factors influencing the preparation of financial reports by Government Ministries/Agencies. The presentation of financial reports by government ministries/agencies is crucial to accountability and stakeholder trust. Numerous studies have been conducted to gain a deeper understanding of the factors affecting the preparation of these financial reports. This research utilizes a literature review method, gathering data through the exploration and analysis of journal articles and books and relevant theoretical sources related to policies issued by the government (agency), information technology, and human resource competence. This study is descriptive and conceptual, not involving empirical research or primary data analysis. It can provide a better understanding of the factors contributing to the preparation of financial reports, thereby assisting stakeholders, such as the government in policymaking, in producing high-quality financial reports. The analysis results indicate that government policies (agency), information technology, and human resource competence positively influence the preparation of Government Ministries/Agencies' Financial Reports, particularly on the quality of the generated reports